Feasibility of a Complex Setting for Assessing Sleep and Circadian Rhythmicity in a Fragile X Cohort - Dueck, Alexander; Reis, Olaf; Bastian, Manuela; van Treeck, Lucas; Weirich, Steffen; Haessler, Frank; Fiedler, Andreas; Koelch, Michael; Berger, Christoph (Frontiers in Psychiatry, 2020)
Introduction: Sleep, circadian rhythms, (mental) health and development are assumed to be intertwined, but are hard to measure in Fragile X individuals. As sleep and circadian parameters need to be observed in complex settings, the feasibility of measurements for people with Fragile X was tested. Findings from this pilot study can be used to estimate sample sizes for studies to come. Methods and sample: 9 individuals (male and female) with full mutation of the FMR1 gene were integrated in the study and underwent the complex setting including actigraphy, sleep log, 24 h saliva sampling to examine profiles of melatonin and cortisol, and polysomnography. Results: n=7 PSGs, n=8 sleep logs, n=8 saliva profiles, n=7 actigraphy profiles and n=6 complete data sets (mean age 14,87 years (SD 4,12), mean BMI 25,90 (SD 4,44)) were collected. No investigation was interrupted or cancelled during procedure. Discussion: Each investigation and the setting in total were tolerated well by participants and caring systems (parents or care givers). Procedures were adapted to the needs of the participants. Conclusion: All its components and the setting in total are absolutely feasible in the specific population of FXS individuals.